Analysis Of Nursing Clinical Practices In MRS. S With The Innovation Of Free Painting Therapy Using Totebag Media In Patients With Sensory Perception Disorders, Auditory Hallucinations In The Punai Room Of Atma Husada Mahakam RSJD Samarinda - Aldilla Asri Chairunnisa; Arief Budiman; Linda Dwi Novial; Dwi Rahmah Fitriani (International Journal of Health Engineering and Technology, 2026)
Mental disorders, especially schizophrenia, are still a mental health problem with a high prevalence in Indonesia, including in East Kalimantan, with one of the main symptoms being sensory perception disorders of auditory hallucinations that can interfere with psychosocial functions and the patient's ability to control themselves. This scientific paper aims to analyze the effectiveness of an innovative intervention in the form of free painting therapy with totebag media as a non-pharmacological approach in reducing the signs and symptoms of auditory hallucinations. The method used is an analysis of nursing clinical practice through a nursing process approach, with measurement of the level of auditory hallucinations using the Auditory Hallucination Rating Scale (AHRS) 11-item questionnaire which was carried out three times during three free painting therapy interventions. The evaluation results showed a significant decrease in the auditory hallucination score, from an initial score of 33 before the intervention to 7 after the entire series of interventions were given, which was characterized by a reduction in the frequency, duration, and intensity of hallucinations and an increase in the patient's ability to control and divert attention from hallucinations. Free-form painting therapy using tote bags is effective as a non-pharmacological nursing intervention in reducing the intensity of auditory hallucinations and can be used as an alternative activity therapy in psychiatric nursing practice.